2013
DOI: 10.1158/0008-5472.can-12-2269
|View full text |Cite
|
Sign up to set email alerts
|

Systems Analysis of BCL2 Protein Family Interactions Establishes a Model to Predict Responses to Chemotherapy

Abstract: Apoptotic desensitization is a hallmark of cancer cells, but present knowledge of molecular systems controlling apoptosis has yet to provide significant prognostic insights. Here, we report findings from a systems study of the intrinsic pathway of apoptosis by BCL2 family proteins and clinical translation of its findings into a model with applications in colorectal cancer (CRC). By determining absolute protein quantifications in CRC cells and patient tumor samples, we found that BAK and BAX were expressed more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(233 citation statements)
references
References 46 publications
8
223
0
2
Order By: Relevance
“…Indeed, with such quantitative signal transduction models, we were previously able to predict patient specific susceptibility to chemotherapy [31,44,54,84,85]. It is therefore expected that these models in combination with biomolecular studies that investigate molecular mediators of apoptosis can further help to identify patient more vulnerable to DOX-induced cardiac apoptosis and DCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, with such quantitative signal transduction models, we were previously able to predict patient specific susceptibility to chemotherapy [31,44,54,84,85]. It is therefore expected that these models in combination with biomolecular studies that investigate molecular mediators of apoptosis can further help to identify patient more vulnerable to DOX-induced cardiac apoptosis and DCM.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of cancer cells this mechanism was coined as apoptosis priming, aiming to explain why cancer cells are more susceptible to chemotherapy than normal cells. Specifically, proponents of the priming hypothesis such as the Letai group suggest that cancer cells increase their apoptosis likelihood in response to continuous somatic attack by the immune system [45,54], making them more likely than somatic cells to respond to cytotoxic chemotherapy. Indeed, we observe some parallelism between cancer cells primed by somatic apoptosis [45,55] and cardiomyocyte being exposed to (sub-lethal) DOX with respect to metabolic programming and apoptosis sensitization ( Figure 2).…”
Section: Does Dox Exposure Change Apoptosis Likelihood To Later Somatmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multiple studies have shown that patient-specific differences in the dynamic behaviour of these signalling networks underlie individual pathogenetic changes and disease manifestation (Fey et al, 2015;Flanagan et al, 2015;Lindner et al, 2013;Murphy et al, 2013). For example, a dynamic model of the JNK pathway could predict the survival probabilities of cancer patients in neuroblastoma, a common childhood cancer (Fey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all the personalised models mentioned are based on this simple principle of directly using the measured mRNA or protein concentrations as static parameters in the model (Fey et al, 2015;Flanagan et al, 2015;Lindner et al, 2013;Murphy et al, 2013). Thus, all these personalised models are based on the assumption that the Supported by EU FP7 grant "SynSignal" (No.…”
Section: Introductionmentioning
confidence: 99%